Analysis of Rhetorical Devices Used by Alex Hormozi and Lewis Howes - Hung Lee Prianka (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study is about the use of rhetorical devices in podcasts, entitled, How They Keep You POOR! (Watch This To Become A MILLIONAIRE In 2023) | Alex Hormozi. The purpose of this study is to analyze types of rhetorical devices and find the differences and similarities used by Lewis and Alex. The present study employs 15 rhetorical devices by McGuigan (2007) to identify the rhetorical devices used in the podcast. Podcast’s transcripts were examined using a qualitative approach to find the rhetorical devices. The result of the findings is Lewis uses 4 rhetorical devices: hyperbole, hypophora, allusion, exemplum, where Alex uses 9 rhetorical devices: hyperbole, hypophora, rhetorical question, distinctio, imagery/simile, metaphor, allusion, sententia, exemplum. Understatement, litotes, procatalepsis, analogy, and eponym are not used in the podcast. In the difference, Lewis did not use rhetorical question, distinctio, imagery/simile, metaphor, and sentenia. However, in the similarity both Lewis and Alex used hyperbole, hypophora, allusion, and exemplum. In conclusion, hyperbole and exemplum can be used as the tools for the speaker’s to inspire the audience because it is exaggerating statements and gives the related matter in the real-life context which can grab the audience’s attention.